2019
DOI: 10.1111/ans.14963
|View full text |Cite
|
Sign up to set email alerts
|

Safety of laparoscopic appendicectomy during pregnancy: a systematic review and meta‐analysis

Abstract: Background Acute appendicitis is the most common non‐obstetric surgical presentation during pregnancy. There were concerns that laparoscopic appendicectomy increases the risk of foetal loss compared to an open approach. Therefore, with recent advances in perioperative care, it is likely the risk has changed. Here, we performed an updated meta‐analysis assessing the safety of laparoscopic appendicectomy in pregnant women. Methods A meta‐analysis was performed according to Preferred Reporting Items for Systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Nowadays, there is deficient testimony to point out the optimal operation of appendicitis in pregnancy because large RCTs are difficult to conduct in pregnant women. In recent years, systematic reviews and meta-analyses also had no consensus on whether to choose LA or OA (15)(16)(17). Under such an unclear situation, further explorations for pregnant appendicitis are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, there is deficient testimony to point out the optimal operation of appendicitis in pregnancy because large RCTs are difficult to conduct in pregnant women. In recent years, systematic reviews and meta-analyses also had no consensus on whether to choose LA or OA (15)(16)(17). Under such an unclear situation, further explorations for pregnant appendicitis are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical practice, LA and OA both have been performed in patients, whether it is the early or the third trimester. Many systematic reviews have been published to evaluate the effects of the two surgical methods on the fetus and pregnant women, but until now there have been no consistent conclusions (15)(16)(17). In the past 2 years, some clinical studies evaluating the two operations have tended to show no significant difference in obstetric outcomes, such as fetal loss and pre-term delivery (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent indications for surgery during pregnancy are infections such as acute appendicitis and cholecystitis [5][6][7][8][9][10][11][12][13][14]; pregnant women may also require acute surgical intervention for ovarian disorders and bowel obstruction, as well as for traumatological or oncological indications [11]. Any kind of pathology can occur in pregnant women and require immediate surgical treatment and optimized interdisciplinary management to achieve maximum safety for both mother and fetus, to avoid teratogenous medication, fetal acidosis and hypoxemia, and adverse pregnancy outcomes such as miscarriage, stillbirth or premature birth [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there have been no deaths [ 8 , 17 , 18 , 31 , 32 ]. On the contrary, a meta-analysis of 17 observational studies showed that LA had a higher risk of fetal loss (5.69% vs. 3.73%) but a low preterm delivery (2.84% vs. 8.99%) [ 40 ]. Nearly one out of twenty women who underwent appendectomy can have a complicated obstetrics course in the form of preterm labor, cervical incompetence, vaginal infection, and sepsis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%